2006
DOI: 10.1002/zamm.200510293
|View full text |Cite
|
Sign up to set email alerts
|

Wax diffusivity under given thermal gradient: a mathematical model

Abstract: In this paper we describe how to obtain wax diffusivity and solubility in a saturated crude oil using the measurements of solid wax deposit in the experimental apparatus known as cold finger. Assuming that migration of dissolved wax is primarily driven by thermal gradients, mathematical models are derived relating the deposit growth rate to the above mentioned quantities. We will investigate the case in which the oil is not agitated. The stirred case is studied in part II. Comparisons with available experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…This can be explained by the fact that due to a greater temperature difference, a longer amount of time is required for the mixture to reach thermal equilibrium. This translates to a greater crystallisation time, allowing a greater amount of wax crystals to form [13]. In addition to this, the greater temperature gradient which the mixture is exposed to further encourages the formation of new crystals or nucleation, which enables a greater rate of formation of the wax crystals [13].…”
Section: Effect Of Chilling Temperaturementioning
confidence: 99%
“…This can be explained by the fact that due to a greater temperature difference, a longer amount of time is required for the mixture to reach thermal equilibrium. This translates to a greater crystallisation time, allowing a greater amount of wax crystals to form [13]. In addition to this, the greater temperature gradient which the mixture is exposed to further encourages the formation of new crystals or nucleation, which enables a greater rate of formation of the wax crystals [13].…”
Section: Effect Of Chilling Temperaturementioning
confidence: 99%
“…As the dissolved wax reaches the cold finger surface it precipitates, forming a layer of deposit that is subsequently collected and weighed. In [7], [8] two mathematical models for the cold finger apparatus have been proposed, distinguishing between two different situations : (i) the oil is immobile (ii) the solution is stirred.…”
Section: The Cold Finger Devicementioning
confidence: 99%
“…The main scope is to determine predictive formulas for the wax deposit and to use them for deducing the values of wax solubility c s and liquid wax diffusivity D. In [7] it has been shown that for typical temperature ranges of cold finger experiments wax solubility can be considered as a linear function of temperature. Therefore we write…”
Section: The Cold Finger Devicementioning
confidence: 99%
See 2 more Smart Citations